(untitled) (Journal of Partial Differential Equations, 1998)
In this paper, for a class of exterior force term 2s²W^'_s,s we analyse the existence of unstable modes of linearized Navier-Stokes Equations (NSE), and associate them with integer points in plane. Furthermore we give the lower boundary dimension estimation of the attractor of NSE. Liu discussed the condition where the exterior force term is W^'_0,s in (1, 2), but his method can't be extended to the condition where the exterior force term is W^'_s_1,s_2 (s_1 ≠ 0, s_2 ≠ 0). So this paper may look as the extention of [1, 2]. The method which we give in this paper has direct application for further study of other properties of NSE (such as Hopf bifurcation). See [3].